Philippians - Belleville, Linda L. (Lutterworth Press, 2022)
"In this accessible and erudite commentary, the respected New Testament scholar Linda Belleville shows how Paul's letter to the Philippians provides a unique opportunity to see the similarities between the culture of his day and ours and to understand not only what is needed to cope in a hostile society but also to be bold in sharing the sole hope for our global world: knowing Christ and eternal citizenship in heaven. Philippians was written while Paul was imprisoned in the imperial barracks, awaiting the outcome of a life-or-death trial. His most beloved church was facing strong opponents without and selfish division within. Paul's strategy is to remind the church of the reasons to rejoice and forgo selfish opinion differences. There is much cause to rejoice because, despite imprisonment, the gospel had reached the entire imperial guard and emboldened Christians everywhere to boldly proclaim Christ; even if he dies, Paul's ministry of preaching Christ will continue. Yet the Philippians'best exemplar is Christ himself, who, while enjoying his heavenly riches, willingly took on the human condition with its pain, suffering, and death so that they might gain their own heavenly riches."--Publisher.